Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1021/ja0692130
|View full text |Cite
|
Sign up to set email alerts
|

Dilithiation of Bis(benzene)molybdenum and Subsequent Isolation of a Molybdenum-Containing Paracyclophane

Abstract: The homoleptic sandwich complex bis(benzene)molybdenum, [Mo(eta6-C6H6)2], was successfully dilithiated by employing an excess of BuLi in the presence of N,N,N',N'-tetramethylethylenediamine (up to 6 equiv each) at slightly elevated temperatures furnishing the highly reactive, ring metalated species [Mo(eta6-C6H5Li)2].tmeda in high yields. Alternatively, this compound was synthesized upon prolonged sonication with 5 equiv of tBuLi/tmeda without heating. An X-ray crystal structure determination revealed a symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 65 publications
(42 reference statements)
4
29
1
Order By: Relevance
“…[6d, 8] Irradiation of a solution of 1 in [D 6 ]benzene afforded 3 with concomitant evolution of gaseous H 2 . Monitoring the reaction by 1 H NMR spectroscopy revealed the absence of any soluble byproducts, thus indicating quantitative conversion.…”
mentioning
confidence: 99%
“…[6d, 8] Irradiation of a solution of 1 in [D 6 ]benzene afforded 3 with concomitant evolution of gaseous H 2 . Monitoring the reaction by 1 H NMR spectroscopy revealed the absence of any soluble byproducts, thus indicating quantitative conversion.…”
mentioning
confidence: 99%
“…The rms deviation from a plane of the five atoms Pt1, P1, P2, C1, and Si1 is 0.0599 Å , with the largest individual deviation of 0.0717(14) Å found for P2, illustrating a planar coordination of the d 8 metal cation. The Si atom is in a distorted tetrahedral environment, with angles spanning from 98.9(2)°(C7-Si1-C13) to 117.56 (16)…”
Section: Resultsmentioning
confidence: 99%
“…Independent of our work, Braunschweig et al had attempted the synthesis of sila[1]molybdarenophanes using Ph 2 SiCl 2 , iPr 2 SiCl 2 , and Me 2 SiCl 2 before but did not find any direct evidence for the formation of the targeted species. 16 Only in the case of iPr 2 SiCl 2 had a product been identified, the 1,1 0 -disubstituted bis(benzene)molybdenum derivative [{(CliPr 2 Si)C 6 H 5 } 2 Mo], and its synthesis was subsequently optimized. We had shown that species 1 can be obtained, with the main impurities presumably being 1,1 0 -disubstitued bis(benzene)molybdenum species.…”
Section: Resultsmentioning
confidence: 99%
“…26-28 For example, the bis(benzene)molybdenum complex was metalated with 2 equiv t-BuLi to give the diionic intermediate 10, which was subjected to react with i-Pr 2 SiCl 2 to give complex 11; the yield of the latter step is 37% (eq 10). 28 …”
Section: Simentioning
confidence: 99%